Financial Performance Evaluation as a Determining Factor of Stock Prices : Case Study of PT Bank Mandiri Tbk - Ermaini Ermaini; Trie Hierdawati; Agus Santoso (International Forum of Researchers and Lecturers, 2025)
This research focuses on analyzing the impact of fundamental financial ratios on stock prices in the banking sector, specifically examining PT. Bank Mandiri Tbk. The key financial ratios investigated include Return On Assets (ROA), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), and the ratio of Operating Expenses to Operating Income (BOPO). The study employs a quantitative descriptive research method, utilizing secondary data sourced from annual reports spanning the period from 2014 to 2023. Multiple linear regression analysis is utilized as the primary analytical tool to address the research questions and hypotheses. The findings of the study reveal that the independent variables—ROA, LDR, NPL, and BOPO—significantly influence stock prices, both in isolation and collectively. This indicates that these financial ratios are critical indicators for investors and stakeholders when evaluating the performance and market value of banking institutions. The research highlights the importance of these financial metrics in shaping market perceptions and stock valuations, providing valuable insights for investors, financial analysts, and decision-makers in the banking industry. Furthermore, the study contributes to the existing body of knowledge regarding the relationship between financial performance indicators and stock market behavior. By emphasizing the correlation between these ratios and stock prices, the research underscores the necessity for stakeholders to monitor and analyze these key financial metrics to make informed investment decisions. Overall, the results affirm the relevance of fundamental financial ratios in assessing the financial health and competitive positioning of banks, particularly in the context of PT. Bank Mandiri Tbk. This analysis not only enriches the literature on banking finance but also serves as a practical guide for stakeholders aiming to optimize their investment strategies based on financial performance indicators.